(untitled) (Revista CICSA online, serie nouă/ CICSA Journal online, New Series, 2025)
This article examines the implicit interaction between Emperor Marcus Aurelius and his former teacher Fronto in their correspondence De nepote amisso. The assumption I am arguing for is that Fronto writes his own letter of consolation, as the emperor’s response seems too inadequate to him. His highly emotional letter also requires explanation, as it is not a traditional letter of condolence that can be classified into conventional rhetorical categories. Fronto implicitly conveys several messages to the emperor which are as follows: Emotional grief is justified in this situation; philosophy is unable to offer comfort; the parents of the deceased child can only offer each other comfort; Victorinus’ virtuous character deserves to be held in high esteem by the emperor. Fronto, having reached the end of his life, finds comfort solely in his virtuous life.